Der Abschreckungseffekt auf die Grundrechtsausübung Strukturen eines verfassungsrechtlichen Arguments - Staben, Julian (Internet und Gesellschaft, 2017)
Julian Staben examines chilling effects, framed as deterrence-based lines of argument, in the jurisprudence of the Bundesverfassungsgericht (German Federal Constitutional Court) and compares them with the jurisprudence of the US Supreme Court. Chilling effects follow distinct patterns when it comes to online behaviour and emerging digital practices and therefore call for their constitutional reassessment. Julian Staben's work enables a more methodologically reflective use of these arguments in the judicial discourse.